SURVEI MOTIVASI TERHADAP SENAM AEROBIK DI KLUB SENAM SE-KOTA PONTIANAK - Ningsih, Emilia Gripa; Kresnadi, Heri; ., Wahyudi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2014)
The research problem is how to motivate the club gymnastics aerobics in Pontianak. Order to determine how motivated the club gymnastics aerobics at Pontianak. The research method was descriptive quantitative research. The population was aerobics participants Pontianak city, with a sample of 58 respondents. Data analysis using descriptive percentages. The results showed an average score of motivation in the following aerobic exercise is the percentage rate of 25.64 to 80.13% categorized in higher classification. The motivation appears influenced some indicators supporting among others: the average was 3:29 with physiological indicators percentage rate 82.25% classification categorized in high, averaging 3.84 with a security indicator is the percentage rate of 76.80% categorized in a higher classification, the average social indicators is 7.53 with a percentage rate of 94.13% categorized in a very high classification, the average indicator of self-esteem is 4.45 with a percentage rate of 74.16% categorized in a higher classification, the average indicator of self-actualization is 6.51 with a percentage rate of 72.33% categorized in a higher classification. Keywords : Motivation, Gymnastics, Aerobics. Abstrak: Masalah penelitian ini adalah bagaimana motivasi terhadap senam aerobik pada klub senam Se-Kota Pontianak. Tujuan untuk mengetahui seberapa besar motivasi terhadap senam aerobik pada klub senam Se-Kota Pontianak. Metode penelitian adalah penelitian deskriptif kuantitatif. Populasi penelitian ini adalah peserta senam aerobik se-kota Pontianak, dengan jumlah sampel 58 responden. Analisis data menggunakan deskriptif persentase. Hasil penelitian menunjukan rata-rata skor motivasi dalam dalam mengikuti senam aerobik adalah 25.64 dengan tingkat persentase sebesar 80.13% dikatagorikan dalam klasifikasi tinggi. Adapun motivasi ini muncul dipengaruhi beberapa indikator pendukung antara lain: rata-rata indikator fisiologi adalah 3.29 dengan tingkat persentase 82.25% dikatagorikan dalam klasifikasi tinggi, rata-rata indikator keamanan adalah 3.84 dengan tingkat persentase 76.80% dikatagorikan dalam klasifikasi tinggi, rata-rata indikator sosial adalah 7.53 dengan tingkat persentase 94.13% dikatagorikan dalam klasifikasi sangat tinggi, rata-rata indikator harga diri adalah 4.45 dengan tingkat persentase 74.16% dikatagorikan dalam klasifikasi tinggi, rata-rata indikator aktualisasi diri adalah 6.51 dengan tingkat persentase 72.33% dikatagorikan dalam klasifikasi tinggi. Kata kunci : Motivasi, Senam, Aerobik